Subjectness and paternalism of modern youth in the system of professional career formation (The Journal of Psychology and Sociology, 2017)
In the introduction we specify the object of research – the young people at the stage of inclusion in professional and career space. The aim of the study is to examine the conditions for the formation of subject, that is the responsible attitude of young people towards privacy and disclosure of paternalistic attitudes of the modern youth.The main part disclosed understanding of subject as an independent, respon-sible for their own choice person with an active lifestyle. It was determined that young people due to the peculiarities of their social position are especially vulner-able to threats of formation of dependent behavior, which develops as a result of paternalistic expectations, trustee attitude of social institutions to their conditions of life.It is stated that the implementation and building of professional career helps to overcome indecision and gives the opportunity to include young people in the system of industrial relations, self-designing their way of life, to engage in competi-tive interactions with other subjects of career processes. The development of career competence facilitates the formation of young people as full-fledged subjects of career advancement.The necessity of development of the subject education of youth with the aim of developing their values of personal uniqueness and formation of active life posi-tion is set.The essence of tolerance as a necessary indicator of social maturity of a person that is able to withstand the pressure of divergent social attitudes, and the need to create a tolerant environment in which there are opportunities for equal subject-subject interactions are disclosed.
Keywords: subject; paternalism; youth; career; career competence; subject education; tolerance.